Micro Enterprises, Human Agency and Business Success: Evidence from Malaysia - Jiang, Yue; Wang, Chunyan (International Journal of Global Economics and Management, 2024)
Using Human agency theory, this study aimed to investigate rovide a nuanced understanding of how microentrepreneurs navigate the complexities of starting and managing their businesses. It also intended to discover the characteristics of the human agency that contribute to the success of a micro business, as well as the life experiences that micro entrepreneurs learned. This qualitative study employs structured interviews with 41 microentrepreneurs from various industries in Malaysia. Participants' ages ranged from 22 to 34, with business experience varying from 1 to 4 years. The data were analyzed thematically to identify key patterns and insights into the cognitive processes of intentionality, forethought, self-reactiveness, and self-reflection, as well as the influence of life circumstances on entrepreneurial behavior. The findings reveal that microentrepreneurs are highly adaptable, with motivations deeply rooted in personal experiences and life circumstances. Key motivations include financial independence, family support, and the desire to create a personal legacy. The cognitive processes of intentionality, forethought, self-reactiveness, and self-reflection are pivotal in shaping entrepreneurial actions. Life experiences such as previous work, education, and significant life changes profoundly influence these cognitive processes.